An Organic Down‐Converting Material for White‐Light Emission from Hybrid LEDs. (16th September 2014) - Findlay, Neil J.; Bruckbauer, Jochen; Inigo, Anto R.; Breig, Benjamin; Arumugam, Sasikumar; Wallis, David J.; Martin, Robert W.; Skabara, Peter J.
<x xml:space="preserve">Abstract</x> A novel BODIPY‐containing organic small molecule is synthesized and employed as a down‐converting layer on a commercial blue light‐emitting diode (LED). The resulting hybrid device demonstrates white‐light emission under low‐current operation, with color coordinates of (0.34, 0.31) and an efficacy of 13.6 lm/W; four times greater than the parent blue LED. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>